PENGARUH QUALITY OF WORK LIFE, KEADILAN ORGANISASIONAL TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABLE MEDIASI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI KEPULAUAN RIAU - Destriyanti, Putri; Wihadanto, Ake; Arie Wibowo Khurniawan, I (Program Studi Manajemen FEBM UMRAH, 2024)
This research is used for explanatory or confirmatory purposes, namely explaining the causal relationship between variables through hypothesis testing. This research is correlational in nature, namely research that attempts to see whether two or more variables are related and what direction the relationship takes. In this study, the population was 273 employees of the Riau Islands Province Department of Industry and Trade. In this study the population was 273 employees of the Riau Islands Province Industry and Trade Service. Quality of Work Life has a positive and significant effect by mediating job satisfaction on employee performance. Organizational justice has a positive and significant mediating effect on job satisfaction on employee performance.